Deeper and Deeper on the Role of BK and Kir4.1 Channels in Glioblastoma Invasiveness: A Novel Summative Mechanism? - Brandalise, Federico; Ratto, Daniela; Leone, Roberta; Olivero, Federico; Roda, Elisa; Locatelli, Carlo Alessandro; Grazia Bottone, Maria; Rossi, Paola (Frontiers in Neuroscience, 2020)
In the last decades, increasing evidences has revealed that a large number of channel protein and ion pumps have an impaired expression in cancers and this misregulation is responsible for high proliferative rate as well as migration and invasiveness in cancer. Due to that, the term oncochannelopathies has been recently coined. In glioblastoma (GBM), the most invasive and aggressive primary brain tumor, GBM cells modify their ionic equilibrium in order to change their volume as a necessary step prior to migration. In this scenario, BK channels are overexpressed in biopsies from patients and Kir 4.1, a largely expressed ion channel in glia is downregulated in GBM cells. Despite a large body of works showing an implication of BK channels in migration upon artificial intracellular calcium rise, little is known about how this channel can act under GBM resting membrane potential (RMP) in relation to other channels that are constitutively open, such as Kir 4.1. In this review we proposed that the residual fraction of functionally active Kir 4.1 channels exerts a small, but continuous, efflux of potassium at the more depolarized RMP of GBM cells. On top of that, coinciding with transient mechanic membrane stress and intracellular raise of calcium concentration, BK channel can be active for a short time window to provide a massive, fast-acting cytosolic water loss in order to reduce the volume of the cell (cell shrinkage), a necessary step for migration along the brain parenchyma.